PENINGKATAN DAYA SAING UMKM MELALUI PENDAMPINGAN IMPLEMENTASI AKUNTANSI SYARIAH DI LINGKUNGAN YAYASAN AL-BAHJAH CIREBON - Ramsito, Ramsito (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service aims to increase the knowledge and skills of Al-Bahjah Foundation UMKM players regarding the implementation of sharia accounting. This program is expected to encourage consistent application of sharia accounting principles and improve UMKM financial management, thereby producing financial reports that are accurate and comply with sharia standards. The implementation method used is participatory and integrated, starting with a needs survey, followed by intensive training, workshops and mentoring. The material provided includes basic sharia accounting principles, financial recording and reporting practices, as well as the use of sharia accounting software. Monitoring and evaluation is carried out through pre-test, post-test, implementation observation, and participant satisfaction questionnaires. Service results are measured based on increased knowledge, consistent application, as well as increased transparency and competitiveness of UMKM.